Preparation and application of composite surface modification modified lithium manganate positive electrode material

CN123017917APending Publication Date: 2026-10-30GUIZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611088742.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]针对现有技术的不足,本发明提供了一种复合表面修饰改性锰酸锂正极材料的制备及应用,解决了现有LiMn2O4正极材料在高电压长循环过程中Mn溶出和界面副反应严重、常规包覆层结合力弱且离子传导性差的问题

Benefits of technology

1、本发明通过采用含氟和/或含磷的界面过渡层与LiAlO2/LaAlO3复合涂层的三层结构设计,在LiMn2O4颗粒表面构建了化学键合的界面保护体系,界面过渡层中的F或P元素以离子形式扩散进入表层晶格,降低了表面活性,减少了Mn3+歧化反应导致的Mn溶出,复合涂层中LiAlO2提供快速的Li+传导通道,LaAlO3作为致密惰性相阻挡电解液侵蚀,两者协同作用使正极材料在0.5C倍率下循环200圈后的容量保持率可达到86%以上,相比未改性样品提高了约8个百分点,延长了电池的长循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017917A_ABST
    Figure CN123017917A_ABST
Patent Text Reader

Abstract

The present application relates to the field of lithium ion battery cathode material, discloses a kind of preparation and application of composite surface modification modified lithium manganate cathode material, preparation method includes: LiMn2O4 powder is added in the aqueous solution containing organic acid and fluorine-containing compound and / or phosphorus-containing compound and is handled, obtain the powder that fluoride and / or phosphate are deposited in acid treatment;The powder is activated and is handled in inert atmosphere 200~350 ℃;Again, the activated powder is immersed in the precursor solution containing Al 3+ And La 3+ , after solvent is evaporated dry, sintering is carried out in 400~900 ℃ air atmosphere, make Al 3+ And La 3+ In-situ conversion LiAlO2 / LaAlO3 Composite coating.The present application inhibits Mn dissolution by interface transition layer, utilizes composite coating to give consideration to ion conduction and electrolyte barrier effect, enhances the chemical binding force of coating and matrix, improves the capacity retention rate after 0.5C cycle 200 cycles and high rate discharge specific capacity of material.Preparation process step is simple, condition is mild, and is suitable for LiMn2O4 matrix synthesized by different types of manganese source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode materials, specifically to the preparation and application of a composite surface-modified lithium manganese oxide cathode material. Background Technology

[0002] LiMn2O4, as a spinel-structured lithium-ion battery cathode material, boasts advantages such as low cost, good safety, and environmental friendliness, leading to its widespread application in power batteries and energy storage. However, this material suffers from rapid capacity decay during long-cycle operation, hindering its further adoption in high-energy-density batteries. The main factors contributing to capacity decay include: Mn2O4 during charge and discharge processes... 3+ A disproportionation reaction occurs to generate Mn. 2+ Mn 2+ Dissolution into the electrolyte leads to the loss of active materials; the Jahn-Teller effect under deep discharge conditions causes the spinel structure to transform from a cubic to a tetragonal phase, resulting in lattice distortion and particle cracking; and side reactions occur at the electrode-electrolyte interface under high voltage, forming a high-impedance interfacial film on the particle surface. To address the aforementioned issues, researchers have explored various modification strategies. Element doping is a common approach, where introducing elements such as Al, Mg, and Cr into the LiMn2O4 lattice to replace some Mn sites can stabilize the spinel structure and suppress Mn dissolution. However, doping typically requires adjustments to the synthesis process and cannot completely resolve interfacial side reactions. Another approach is to coat the particle surface with an inert oxide layer, such as Al2O3, ZrO2, or TiO2, to reduce direct contact between the electrolyte and the active material through physical barriers. However, traditional oxide coatings have the following limitations: the coating layer and the LiMn2O4 substrate are physically adsorbed or weakly chemically bonded, making interfacial separation prone to occur during cycling; single oxide coatings struggle to balance ion conductivity and chemical stability; transition metal oxide coatings themselves have poor ion conductivity, which, while improving stability, introduces additional interfacial impedance, leading to a decrease in rate performance. Furthermore, most current coating processes involve organic solvents or complex precursor treatment steps, requiring high process control and hindering large-scale production. Summary of the Invention

[0003] To address the shortcomings of existing technologies, this invention provides a method for preparing and applying a composite surface-modified lithium manganese oxide cathode material, which solves the problems of severe Mn dissolution and interfacial side reactions, weak bonding force of conventional coating layers, and poor ion conductivity in existing LiMn2O4 cathode materials during high-voltage long-cycle processes.

[0004] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for preparing a composite surface-modified lithium manganese oxide cathode material, using the following technical solution: A composite surface-modified lithium manganese oxide cathode material includes LiMn2O4 particles as a matrix and a composite coating covering the surface of the LiMn2O4 particles; the composite coating is composed of a mixture of in-situ generated LiAlO2 and LaAlO3; a fluorine-containing and / or phosphorus-containing interfacial transition layer is formed between the LiMn2O4 particles and the composite coating; the cathode material has an initial charge-discharge coulombic efficiency of not less than 95% in a 0.1C rate and a voltage range of 3.0–4.3V.

[0005] By adopting the above technical solution, this invention employs a three-layer structure design with LiMn2O4 as the core, a fluorine- and / or phosphorus-containing interfacial transition layer as the intermediate layer, and a LiAlO2 and LaAlO3 composite coating as the shell. The role of the interfacial transition layer is that fluorine or phosphorus elements diffuse into the LiMn2O4 particle surface lattice in ionic form during the in-situ deposition process under acid treatment, occupying some oxygen or Mn sites and forming stable chemical bonds, thereby effectively reducing particle surface activity and inhibiting Mn oxidation. 3+ The disproportionation reaction and dissolution of Mn occur. Simultaneously, this interfacial layer chemically bonds with the composite coating during subsequent sintering, enhancing the adhesion between the coating and the substrate. Regarding the composite coating, LiAlO2, as a fast ion conductor, exhibits good Li... + The high conductivity reduces polarization at high rates; LaAlO3, as a perovskite-type inert phase, has a dense structure and good chemical stability, which can significantly inhibit the erosion of the positive electrode surface by the electrolyte. Both are uniformly mixed at the nanoscale in the coating to form an interpenetrating network structure, providing rapid Li... + The coating acts as a transport channel, while also forming a rigid mechanical protective layer. The in-situ formation method ensures that the coating and substrate form a chemical bond through lattice matching, avoiding the interface separation problems encountered in physical coating. This structural synergy enables the material to achieve an initial coulombic efficiency of over 95% at 0.1C, indicating that interfacial side reactions are effectively suppressed.

[0006] Preferably, the molar ratio of Al to La in the composite coating is (0.5–2):(0.5–2), and the total mass of the coating accounts for 0.5%–8% of the total mass of the cathode material.

[0007] By adopting the above technical solution, when the Al:La molar ratio is controlled within a near equimolar range, the LiAlO2 and LaAlO3 phases can form a relatively uniform distribution and exhibit lattice matching relationships, which is beneficial for balancing ion transport and structural stability. When the total mass ratio of the coating is too low (below 0.5%), continuous coverage is difficult to achieve, and Mn dissolution remains significant under high-frequency charge-discharge conditions; when the ratio is too high (above 8%), the coating's own resistance increases, and an excessively thick inert layer hinders Li... + Ingress and egress from the substrate lead to a decrease in capacity and rate performance. Experiments show that when the Al:La molar ratio is 1:1 and the total mass of the coating is about 1%–3%, both rate performance and cycle retention reach a relatively optimal range.

[0008] Preferably, the fluorine-containing and / or phosphorus-containing interfacial transition layer is derived from at least one of the following precursors: ammonium fluoride, ammonium dihydrogen phosphate, lithium fluoride, or hydrofluoric acid; the amount of the precursor introduced into the cathode material (in terms of F or P elements) is 0.5%–4% of the mass of the LiMn2O4 matrix.

[0009] The reason for choosing ammonium fluoride or ammonium dihydrogen phosphate as precursors by adopting the above technical solution is that these substances can be uniformly dispersed in ionic form in the aqueous solution system of acid treatment. During the acid washing process, they come into contact with the surface of LiMn2O4 particles along with the organic acid, and achieve adsorption and surface reaction with the help of the acid washing environment. - Or PO4 3- During subsequent activation and sintering, it reacts with Mn or Li sites on the matrix surface to form a chemical bond, rather than a physical residue. Controlling the amount introduced to 0.5%–4% (based on F or P elemental content) can avoid excessive doping leading to surface inertization or the formation of a second-phase impurity. The introduction of fluorine can also replace some lattice oxygen, suppressing Jahn-Teller distortion; the introduction of phosphorus helps form a stable phosphate layer at the interface, further reducing Mn dissolution.

[0010] Secondly, the present invention provides a method for preparing and applying a composite surface-modified lithium manganese oxide cathode material, using the following technical solution: The preparation of a composite surface-modified lithium manganese oxide cathode material includes the following steps: S2. Add LiMn2O4 powder to an aqueous solution containing organic acid and fluorine and / or phosphorus compounds, stir and react at room temperature, and after the reaction is completed, separate, wash and dry to obtain an acid-treated powder with fluoride and / or phosphate deposited on the surface. S3. Place the powder obtained in S2 under an inert atmosphere and keep it at 200–350℃ for 1–3 hours for activation treatment. After cooling, the activated powder is obtained. S4. Add the activated powder to the Al-containing... 3+ and La3+ The precursor solution was impregnated, the solvent was evaporated, and then sintered at 400–900℃ for 2–10 hours in air atmosphere to allow Al to form a precipitate. 3+ and La 3+ The cathode material is obtained by in-situ conversion into a composite coating of LiAlO2 and LaAlO3.

[0011] By employing the above technical solution, step S2 combines organic acid treatment with surface deposition of fluorine / phosphorus compounds in the same aqueous solution. The main role of the organic acid is to remove residual alkaline lithium compounds (LiOH, Li2CO3, etc.) formed on the LiMn2O4 surface during synthesis. These residual lithium compounds can cause irreversible side reactions during subsequent coating sintering and hinder the direct chemical bonding between the coating and the substrate. After removing some of the residual lithium from the surface by dissolving it with organic acid, more clean Mn-O active sites are exposed on the particle surface, which is beneficial for the adsorption of the subsequent coating precursor. Meanwhile, the F present in the solution... - Or PO4 3- Ions, with the aid of an acidic environment, partially replace the OH groups on the particle surface. - or CO3 2- This forms a fluorine / phosphorus-containing deposition layer. This deposition layer exists in the form of chemical adsorption or precipitation, providing an interface anchoring layer for subsequent coating sintering.

[0012] The reason for using an inert atmosphere and low-temperature activation in step S3 is that while the initial acid treatment removes residual lithium from the surface, it also introduces some hydroxyl groups or adsorbed water. Direct high-temperature sintering in air would cause these surface groups to decompose too quickly, leading to localized defects on the surface. Holding the treatment at a gentle temperature of 200–350°C under a nitrogen atmosphere allows for the slow removal of adsorbed moisture and organic residues from the surface, while simultaneously allowing F or P ions to diffuse further into the crystal lattice, forming a stable interfacial transition layer. If the activation temperature is below 200°C, the dehydration and diffusion processes are too slow; if it is above 350°C, it may lead to excessive reconstruction of the surface structure, depleting some of the active lattice oxygen.

[0013] In step S4, the activated powder is immersed in an Al-containing solution. 3+ and La 3+ In a nitrate solution, ultrasonic dispersion is used to uniformly penetrate the intergranular spaces and particle surfaces. After the solvent is evaporated, the nitrate is uniformly loaded onto the particle surface in an amorphous or microcrystalline form. During subsequent air-atmosphere sintering, Al... 3+ and La 3+ The particles react with Li and O on their surface to form LiAlO2 and LaAlO3 in situ. The main process of this chemical reaction can be represented as follows: LiMn2O4+Al(NO3)3+La(NO3)3→LiAlO2+LaAlO3+Mn2O3+NO2↑+O2↑ At sintering temperature, Al 3+ Capturing Li in the surface lattice of LiMn2O4 + LiAlO2 is formed, while La 3+ LiAlO2 combines with adjacent AlO6 octahedra to form LaAlO3. Since both are formed on the same particle surface in situ, LiAlO2 and LaAlO3 interpenetrate at the nanoscale, forming a dense composite coating. This coating is chemically bonded to the substrate, exhibiting superior adhesion compared to physical mixing and deposition methods. Compared to directly physically mixing nano-Al2O3 and La2O3 on the LiMn2O4 surface, the in-situ formed composite coating exhibits a more uniform thickness and fewer grain boundary defects, while avoiding the problems of particle detachment and coating peeling associated with physical coating methods.

[0014] Preferably, in step S2, the organic acid is at least one selected from tartaric acid, citric acid, malic acid, oxalic acid, and acetic acid, and its amount is 0.5%–18% of the mass of LiMn2O4 powder; the fluorine-containing compound is selected from at least one selected from ammonium fluoride, lithium fluoride, and hydrofluoric acid; the phosphorus-containing compound is selected from at least one selected from ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; and the amount of the fluorine-containing compound and / or phosphorus-containing compound (calculated as F or P element) is 0.5%–4% of the mass of LiMn2O4 powder.

[0015] By employing the above technical solution, the intensity of acid treatment can be adjusted by selecting different types and amounts of organic acids. Tartaric acid and citric acid have chelating abilities, which can dissolve residual lithium and react with Mn. 2+ Forming complexes reduces surface Mn loss, making it a suitable primary choice for this process. Oxalic acid, being a strong acid, removes residual lithium more thoroughly, but excessive use may lead to over-etching of the surface. When the amount of organic acid is too low (below 0.5%), the removal of residual lithium on the surface is incomplete, limiting the deposition effect of the interfacial transition layer; when the amount is too high (above 18%), the surface active sites are over-occupied by organic acid anions, which in turn inhibits F. - Or PO4 3- This increases the amount of sediment and adds to the burden of subsequent washing.

[0016] Preferably, in step S2, the concentration of the organic acid solution is 0.5–10 g / L, the solid-liquid ratio is 1 g:20 mL, and the stirring time is 2–4 hours.

[0017] By employing the above technical solution, the concentration of the organic acid solution and the solid-liquid ratio jointly determine the contact efficiency between the acid and the particle surface. When the concentration is below 0.5 g / L, the amount of acid is insufficient to neutralize residual lithium on the surface, resulting in limited treatment effect; when the concentration is above 10 g / L, the acidity is too strong, leading to excessive dissolution of Mn from the surface layer. A stirring time shorter than 2 hours results in insufficient solid-liquid reaction, while a stirring time exceeding 4 hours does not significantly contribute to improving the effect. A 2–4 hour window ensures sufficient reaction without overtreatment.

[0018] Preferably, in step S3, the inert atmosphere is nitrogen, the heating rate is 3℃ / min, the activation temperature is preferably 250–300℃, and the holding time is preferably 2 hours.

[0019] By adopting the above technical solution, controlling the heating rate at 3℃ / min can avoid premature decomposition of the coating precursor due to localized rapid heating. Within the activation temperature range of 250–300℃, surface-adsorbed water and organic residues can be steadily removed, while the diffusion of F or P into the lattice reaches a relatively sufficient level. Diffusion is insufficient below 250℃, and some structural oxygen may begin to be lost above 300℃. Holding at this temperature for 2 hours can balance diffusion depth and industrial production efficiency.

[0020] Preferably, in step S4, the precursor solution is aluminum nitrate and lanthanum nitrate dissolved in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1), with a total metal ion concentration of 0.01–0.5 mol / L; Al 3+ with La 3+ The molar ratio is (0.5–2):(0.5–2), and the total mass of the precursor (based on Al and La nitrates) is 0.1%–10% of the mass of the activated powder.

[0021] By employing the above technical solution, the use of a mixed solvent of deionized water and anhydrous ethanol facilitates the wetting and penetration of the precursor solution onto the particle surface. The addition of ethanol reduces the surface tension of the solution, making it easier for the solution to enter the interparticle voids, thereby achieving a more uniform precursor loading. If the total metal ion concentration is too low (below 0.01 mol / L), the coating loading will be insufficient; if the concentration is too high (above 0.5 mol / L), the precursor is prone to segregation during the drying process, resulting in an uneven coating. The coating loading range of 0.1%–10% can cover different needs from partial coverage to complete coating, with a loading of 1%–3% exhibiting the best overall electrochemical performance in this system.

[0022] Preferably, in step S4, the impregnation is carried out at 60°C with ultrasonic dispersion for 2 hours, and the solvent is evaporated at 120°C with stirring.

[0023] By employing the above technical solution, an impregnation temperature of 60℃ helps to increase the diffusion rate of the precursor solution, and ultrasonic dispersion can break up particle agglomeration, allowing the precursor to adhere uniformly to the surface of individual particles. Maintaining stirring during the evaporation process can prevent local enrichment and ensure that the precursor precipitates in a uniform thin layer on the particle surface, laying the foundation for the formation of a uniform coating.

[0024] Preferably, before step S2, step S1 is included: pre-ball milling or acid washing of LiMn2O4 powder to adjust its surface state.

[0025] By employing the above technical solutions, for LiMn2O4 powder with high surface roughness or a large number of large agglomerated particles, pre-processing with ball milling or dilute acid washing can refine the particles, remove some initial impurities, and reduce the burden of acid treatment in step S2, thereby obtaining a cleaner and more uniform surface, which is beneficial for the uniform construction of subsequent interface transition layers and coatings. However, for LiMn2O4 powder with well-controlled synthesis process and high initial purity, this pretreatment step can be omitted without affecting the process effect.

[0026] This invention provides a method for preparing and applying a composite surface-modified lithium manganese oxide cathode material. It offers the following advantages: 1. This invention employs a three-layer structure design, consisting of a fluorine- and / or phosphorus-containing interfacial transition layer and a LiAlO2 / LaAlO3 composite coating, to construct a chemically bonded interfacial protection system on the surface of LiMn2O4 particles. The F or P elements in the interfacial transition layer diffuse into the surface lattice in ionic form, reducing surface activity and decreasing Mn content. 3+ Mn dissolution caused by disproportionation reaction; LiAlO2 in the composite coating provides rapid Li dissolution. + In the conduction channel, LaAlO3 acts as a dense inert phase to block electrolyte erosion. The synergistic effect of the two allows the capacity retention rate of the cathode material to reach more than 86% after 200 cycles at 0.5C rate, which is about 8 percentage points higher than that of the unmodified sample, thus extending the long cycle life of the battery.

[0027] 2. This invention utilizes an in-situ formation method for the composite coating, Al 3+ and La 3+ During sintering, the coating reacts directly with Li and O on the surface of LiMn2O4 to form LiAlO2 and LaAlO3. The coating is chemically bonded to the substrate, resulting in significantly better adhesion than physical mixing or deposition methods. Meanwhile, the nanoscale interpenetrating structure avoids the contradiction between conductivity and stability in a single coating. Experiments show that when the Al:La molar ratio is 1:1, the discharge specific capacity at a high rate of 5C can reach more than 85mAh / g, while the unmodified sample is only about 75mAh / g, demonstrating a significant improvement in rate performance.

[0028] 3. This invention integrates acid washing to remove residual lithium from the surface, interface layer deposition, and coating impregnation sintering into a single wet chemical process. The steps are simple and do not require expensive equipment; surface purification and F can be achieved simultaneously through organic acid treatment. - / PO4 3- Adsorption followed by inert atmosphere activation further stabilized the interfacial layer structure. The entire process was completed under normal pressure and medium-low temperature conditions, making it easy to scale up for production. It is applicable to LiMn2O4 matrices prepared with different lithium and manganese sources. The modified material obtained under the process conditions of Example 2 achieved a capacity retention rate of 87% after 200 cycles at 0.5C, and showed good batch stability, indicating that the method has reproducibility for practical applications. Attached Figure Description

[0029] Figure 1 This is a comparison chart of the pH values ​​of the LiMn2O4 powder aqueous suspension of the present invention; Figure 2 This is a comparison chart of the stoichiometric ratios of acid-soluble Li and Al on the LiMn2O4 surface under different process conditions of the present invention; Figure 3 The cumulative dissolution curves of Mn from LiMn2O4 in LiPF6 electrolyte at 45℃ under different interface doping conditions of the present invention are shown as changes in storage time. Figure 4 This is a comparison chart showing the impact of the cyclic capacity retention rate of the present invention. Figure 5 This is an electrochemical verification diagram of the synergistic effect of the present invention; Figure 6 This is a comparison chart of the initial charge and discharge performance of the present invention; Figure 7 This is a comparison diagram showing the effect of the surface residual lithium removal efficiency and the influence on the initial electrochemical performance of the present invention; Figure 8 This is a comparison diagram showing the influence of the composite coating on the electrochemical performance of the present invention. Detailed Implementation

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0032] The manganese source is manganese dioxide (CAS1313-13-9). The lithium source is lithium carbonate (CAS554-13-2). The acid modifier is selected from tartaric acid (CAS87-69-4). Citric acid (CAS 77-92-9); Malic acid (CAS6915-15-7). Acetic acid (CAS 64-19-7); Oxalic acid (CAS144-62-7); The fluorine-containing compound is selected from lithium fluoride (CAS7789-24-4); Ammonium fluoride (CAS12125-01-8); Hydrofluoric acid (CAS7664-39-3, concentration 40%). The phosphorus-containing compound is selected from ammonium dihydrogen phosphate (CAS 7722-76-1); Diammonium hydrogen phosphate (CAS7783-28-0); The solvent is deionized water or anhydrous ethanol (CAS64-17-5). The aluminum source is aluminum nitrate (CAS7784-27-2). The lanthanum source is lanthanum nitrate (CAS10277-43-7). The inert gas is high-purity nitrogen (purity ≥ 99.999%). Preparation Example 1: This preparation example provides a method for preparing standard unmodified LiMn2O4, including the following steps: Lithium carbonate and manganese dioxide were weighed in a molar ratio of Li:Mn=1.05:2. The above raw materials were placed in a planetary ball mill and ball milled for 2 hours at a ball-to-material mass ratio of 8:1 and a speed of 300 rpm. Anhydrous ethanol was used as the solvent, and the amount used was 1 times the total mass of the raw materials. After ball milling, the precursor powder was dried at 80°C for 6 hours to obtain the precursor powder.

[0033] The precursor powder was evenly spread in a corundum boat and fed into a tube furnace. Under air atmosphere, the temperature was increased from room temperature to 500°C at a rate of 3°C / min and held at the same temperature for 6 hours for pre-calcination. Then, the temperature was increased to 900°C at the same rate and held at the same temperature for 18 hours for main calcination. After natural cooling to room temperature, unmodified LiMn2O4 powder was obtained.

[0034] Preparation Example 2: This preparation example provides a method for preparing LiMn2O4 with different Li:Mn molar ratios, including the following steps: Lithium carbonate and manganese dioxide were weighed out at molar ratios of Li:Mn = 1.02:2 and Li:Mn = 1.08:2, respectively. The raw materials were placed separately in a planetary ball mill and milled for 2 hours at a ball-to-material mass ratio of 8:1 and a speed of 300 rpm. Anhydrous ethanol was used as the solvent, with an amount equal to the total mass of the raw materials. After milling, the powders were dried at 80°C for 6 hours to obtain two precursor powders with different lithium contents.

[0035] The precursor powders were evenly spread in corundum boats and fed into a tube furnace. Under an air atmosphere, the temperature was increased from room temperature to 500°C at a rate of 3°C / min and held at that temperature for 6 hours for pre-calcination. Then, the temperature was increased to 900°C at the same rate and held at that temperature for 18 hours for main calcination. The furnace was then naturally cooled to room temperature to obtain LiMn2O4 powders with Li:Mn=1.02:2 and Li:Mn=1.08:2, respectively.

[0036] Preparation Example 3: This preparation example provides a method for preparing LiMn2O4 from different manganese sources, including the following steps: Lithium carbonate and manganese tetroxide, as well as lithium carbonate and manganese carbonate, were weighed out according to the molar ratio Li:Mn=1.05:2. The raw materials of the two formulations were placed in a planetary ball mill and ball-to-material mass ratio of 8:1 and a speed of 300 rpm for 2 hours. Anhydrous ethanol was used as the solvent, and the amount used was 1 times the total mass of the raw materials. After ball milling, the raw materials were dried at 80℃ for 6 hours to obtain precursor powders of two different manganese sources.

[0037] The precursor powders were evenly spread in corundum boats and placed in a tube furnace. Under air atmosphere, the temperature was increased from room temperature to 500°C at a rate of 3°C / min, and held at this temperature for 6 hours for pre-calcination. Subsequently, the temperature was increased to 900°C at the same rate and held at this temperature for 18 hours for main calcination. After natural cooling to room temperature, LiMn2O4 powders prepared using manganese tetroxide and manganese carbonate as manganese sources were obtained.

[0038] Preparation Example 4: This preparation example provides a method for preparing a pre-modified fluorine / phosphorus-containing surface deposition layer powder, including the following steps: Tartaric acid was dissolved in deionized water to prepare a tartaric acid solution with a concentration of 2 g / L. Ammonium fluoride or ammonium dihydrogen phosphate was added to the solution and stirred for 20 minutes until completely dissolved. The amount of ammonium fluoride or ammonium dihydrogen phosphate added was 1% of the mass of the subsequently added LiMn2O4.

[0039] Take the unmodified LiMn2O4 powder prepared in Preparation Example 1 and add it to the above mixed solution at a solid-liquid ratio of 1g:20mL. Stir at 500rpm for 3 hours at room temperature. After the reaction is completed, perform vacuum filtration and wash the filter cake thoroughly with deionized water and anhydrous ethanol three times each. Place the filter cake in a forced-air drying oven and dry it at 70℃ for 10 hours to obtain premodified LiMn2O4 powder with fluoride or phosphate deposited on the surface.

[0040] Example 1: This embodiment provides a method for preparing modified LiMn2O4 under standard process conditions, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0041] S2. Dissolve tartaric acid in deionized water to prepare a tartaric acid solution with a concentration of 2.0 g / L. The amount of tartaric acid used is 2% of the mass of LiMn2O4. Add LiMn2O4 powder to the above solution at a solid-liquid ratio of 1 g: 20 mL, and stir at 500 rpm for 3 hours at room temperature. After the reaction is complete, filter under vacuum, wash thoroughly three times each with deionized water and anhydrous ethanol, and dry at 70°C for 10 hours to obtain the acid-treated powder.

[0042] S3. Spread the acid-treated powder evenly in a corundum boat and place it in a tube furnace. First, purge the air with high-purity nitrogen for 30 minutes, then heat to 250°C at 3°C / min under a nitrogen atmosphere, hold for 2 hours, and allow to cool naturally to room temperature to obtain activated powder.

[0043] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 1% of the mass of the activated LiMn2O4 powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 500 °C at 3 °C / min in air atmosphere, hold it at that temperature for 6 hours, and then allow it to cool naturally to room temperature to obtain the modified LiMn2O4 powder.

[0044] Example 2: This embodiment provides a method for preparing fluorine-doped modified LiMn2O4, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0045] S2. Dissolve tartaric acid in deionized water to prepare a tartaric acid solution with a concentration of 2.0 g / L. The amount of tartaric acid used is 2% of the mass of LiMn2O4. Add ammonium fluoride to the above solution, with the amount of ammonium fluoride being 1% of the mass of LiMn2O4, and stir for 20 minutes until completely dissolved. Add LiMn2O4 powder to the mixed solution at a solid-liquid ratio of 1 g: 20 mL, and stir at 500 rpm for 3 hours at room temperature. After the reaction is complete, filter under vacuum, wash thoroughly three times each with deionized water and anhydrous ethanol, and dry at 70°C for 10 hours to obtain an acid-treated powder with fluoride deposited on it.

[0046] S3. Spread the above powder evenly in a corundum boat and place it in a tube furnace. First, purge the air with high-purity nitrogen for 30 minutes, then heat to 250°C at 3°C / min under a nitrogen atmosphere, hold for 2 hours, and allow to cool naturally to room temperature to obtain activated powder.

[0047] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 1% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 500 °C at 3 °C / min in air atmosphere, hold it at that temperature for 6 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0048] Example 3: This embodiment provides a method for preparing phosphorus-doped modified LiMn2O4 with different process parameters, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0049] S2. Dissolve citric acid in deionized water to prepare a 5.0 g / L citric acid solution. The amount of citric acid used is 10% of the mass of LiMn₂O₄. Add ammonium dihydrogen phosphate to the above solution, with the amount of ammonium dihydrogen phosphate being 3% of the mass of LiMn₂O₄, and stir for 20 minutes until completely dissolved. Add LiMn₂O₄ powder to the mixed solution at a solid-liquid ratio of 1 g: 20 mL, and stir at 500 rpm for 3 hours at room temperature. After the reaction is complete, filter under vacuum, wash thoroughly three times each with deionized water and anhydrous ethanol, and dry at 70°C for 10 hours to obtain an acid-treated powder with phosphate deposits.

[0050] S3. Spread the above powder evenly in a corundum boat and place it in a tube furnace. First, purge the air with high-purity nitrogen for 30 minutes, then heat to 300°C at 3°C / min under a nitrogen atmosphere, hold for 2 hours, and allow to cool naturally to room temperature to obtain activated powder.

[0051] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1.5:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 3% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 700 °C at 3 °C / min in air atmosphere, hold it at that temperature for 6 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0052] Example 4: This embodiment provides a method for preparing modified LiMn2O4 under low dosage parameters, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0053] S2. Dissolve malic acid in deionized water to prepare a malic acid solution with a concentration of 0.5 g / L. The amount of malic acid used is 0.5% of the mass of LiMn2O4. Add lithium fluoride to the above solution, with the amount of lithium fluoride being 0.5% of the mass of LiMn2O4, and stir for 20 minutes until completely dissolved. Add LiMn2O4 powder to the mixed solution at a solid-liquid ratio of 1 g: 20 mL, and stir at 500 rpm for 3 hours at room temperature. After the reaction is complete, filter under vacuum, wash thoroughly three times each with deionized water and anhydrous ethanol, and dry at 70°C for 10 hours to obtain an acid-treated powder with fluoride deposited on it.

[0054] S3. Spread the above powder evenly in a corundum boat and place it in a tube furnace. First, purge the air with high-purity nitrogen for 30 minutes, then heat to 200°C at 3°C / min under a nitrogen atmosphere, hold for 3 hours, and allow to cool naturally to room temperature to obtain activated powder.

[0055] S4. Weigh aluminum nitrate and lanthanum nitrate at a molar ratio of Al:La = 0.5:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 0.5% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 400 °C at 3 °C / min in air atmosphere, hold it at that temperature for 10 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0056] Example 5: This embodiment provides a method for preparing modified LiMn2O4 under high dosage parameters, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0057] S2. Oxalic acid was dissolved in deionized water to prepare an oxalic acid solution with a concentration of 10 g / L. The amount of oxalic acid used was 18% of the mass of LiMn2O4. Hydrofluoric acid (40%) was added to the above solution, with the amount of hydrofluoric acid (calculated as pure HF) being 4% of the mass of LiMn2O4. The addition was slow and the mixture was stirred. LiMn2O4 powder was added to the mixed solution at a solid-liquid ratio of 1 g: 20 mL, and the mixture was stirred at 500 rpm for 3 hours at room temperature. After the reaction was completed, the mixture was filtered under vacuum and washed thoroughly three times each with deionized water and anhydrous ethanol. The powder was then dried at 70 °C for 10 hours to obtain an acid-treated powder with fluoride deposits.

[0058] S3. Spread the above powder evenly in a corundum boat and place it in a tube furnace. First, purge the air with high-purity nitrogen for 30 minutes, then heat to 350°C at 3°C / min under a nitrogen atmosphere, hold for 1 hour, and allow to cool naturally to room temperature to obtain activated powder.

[0059] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 2:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 8% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g: 10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 900 °C at 3 °C / min in air atmosphere, hold it at that temperature for 2 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0060] Example 6: This embodiment provides a method for preparing modified LiMn2O4 with mixed doping (fluorine and phosphorus), including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0061] S2. Dissolve acetic acid in deionized water to prepare an acetic acid solution with a concentration of 8.0 g / L. The amount of acetic acid used is 15% of the mass of LiMn2O4. Add ammonium fluoride and ammonium dihydrogen phosphate to the above solution at a mass ratio of 1:1, with a total amount of 2% of the mass of LiMn2O4, and stir for 20 minutes until completely dissolved. Add LiMn2O4 powder to the mixed solution at a solid-liquid ratio of 1 g: 20 mL, and stir at 500 rpm for 3 hours at room temperature. After the reaction is complete, filter under vacuum, wash thoroughly three times each with deionized water and anhydrous ethanol, and dry at 70°C for 10 hours to obtain an acid-treated powder with fluoride and phosphate deposits.

[0062] S3. Spread the above powder evenly in a corundum boat, place it in a tube furnace, first purge the air with high-purity nitrogen for 30 minutes, then heat to 280°C at 3°C / min under a nitrogen atmosphere, hold for 1.5 hours, and cool naturally to room temperature to obtain activated powder.

[0063] S4. Weigh aluminum nitrate and lanthanum nitrate according to a molar ratio of Al:La = 1.2:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 5% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 800 °C at 3 °C / min in air atmosphere, hold it at that temperature for 4 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0064] Example 7: This embodiment provides a method for preparing modified LiMn2O4 without an activation step, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0065] S2. Dissolve tartaric acid in deionized water to prepare a tartaric acid solution with a concentration of 2.0 g / L. The amount of tartaric acid used is 2% of the mass of LiMn2O4. Add LiMn2O4 powder to the above solution at a solid-liquid ratio of 1 g: 20 mL, and stir at 500 rpm for 3 hours at room temperature. After the reaction is complete, filter under vacuum, wash thoroughly three times each with deionized water and anhydrous ethanol, and dry at 70℃ for 10 hours to obtain acid-treated powder (unactivated).

[0066] S3. Skip the activation step.

[0067] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 1% of the mass of the acid-treated powder. Add the acid-treated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 500 °C at 3 °C / min in air atmosphere, hold it at that temperature for 6 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0068] Example 8: This embodiment provides a method for preparing modified LiMn2O4 by low-temperature sintering, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0069] S2. Same as step S2 in Example 2.

[0070] S3. Same as step S3 in Example 2.

[0071] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 1% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 300 °C at 3 °C / min in air atmosphere, hold it at that temperature for 10 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0072] Example 9: This embodiment provides a method for preparing modified LiMn2O4 by high-temperature sintering, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0073] S2. Same as step S2 in Example 2.

[0074] S3. Same as step S3 in Example 2.

[0075] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 1% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 1000 °C at 3 °C / min in air atmosphere, hold it at that temperature for 2 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0076] Example 10: This embodiment provides a method for preparing modified LiMn2O4 with a very small amount of coating, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0077] S2. Same as step S2 in Example 2.

[0078] S3. Same as step S3 in Example 2.

[0079] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.01 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 0.1% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 500 °C at 3 °C / min in air atmosphere, hold it at that temperature for 6 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0080] Example 11: This embodiment provides a method for preparing modified LiMn2O4 with a large amount of coating, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0081] S2. Same as step S2 in Example 2.

[0082] S3. Same as step S3 in Example 2.

[0083] S4. Weigh aluminum nitrate and lanthanum nitrate in a molar ratio of Al:La = 1:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.5 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 10% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g: 5 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 500 °C at 3 °C / min in air atmosphere, hold it at that temperature for 6 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0084] Example 12: This embodiment provides a method for preparing La-rich coated modified LiMn2O4, including the following steps: S1. Take the unmodified LiMn2O4 powder prepared in Preparation Example 1.

[0085] S2. Same as step S2 in Example 2.

[0086] S3. Same as step S3 in Example 2.

[0087] S4. Weigh aluminum nitrate and lanthanum nitrate according to a molar ratio of Al:La = 0.5:1, and dissolve them in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1) to prepare a precursor solution with a total metal ion concentration of 0.1 mol / L. The total mass of aluminum nitrate and lanthanum nitrate is 1% of the mass of the activated powder. Add the activated powder to the precursor solution at a solid-liquid ratio of 1 g:10 mL, and ultrasonically disperse at 60 °C for 2 hours. Then transfer the solution to an oil bath and evaporate the solvent at 120 °C and 500 rpm with stirring. Place the evaporated powder in a corundum boat, heat it to 500 °C at 3 °C / min in air atmosphere, hold it at that temperature for 6 hours, and then allow it to cool naturally to room temperature to obtain modified LiMn2O4 powder.

[0088] Comparative Example 1: Compared with Example 1, the difference is that the S2 acid washing step, the S3 activation step and the S4 coating step were not performed. The unmodified LiMn2O4 powder prepared in Preparation Example 1 was used directly. All other steps are the same.

[0089] Comparative Example 2: Compared with Example 2, the difference is that only the S2 pickling step (using tartaric acid, without adding ammonium fluoride) is performed, and the S3 activation step and S4 coating step are omitted; the rest are the same.

[0090] Comparative Example 3: Compared with Example 2, the difference is that the S2 pickling step (using tartaric acid, without adding ammonium fluoride) and the S3 activation step are performed, but the S4 coating step is not performed. All other steps are the same.

[0091] Comparative Example 4: Compared with Example 2, the difference is that the S2 acid washing step and the S3 activation step are skipped, and the S4 coating step is directly performed on the unmodified LiMn2O4 powder prepared in Preparation Example 1. All other steps are the same.

[0092] Comparative Example 5: Compared with Example 2, the difference is that the S3 activation step is skipped, and only the S2 pickling step and the S4 coating step are performed, while the rest are the same.

[0093] Comparative Example 6: Compared with Example 2, the difference is that only aluminum nitrate (Al:La molar ratio = 1:0) is used in step S4, that is, only LiAlO2 coating is generated and LaAlO3 is not present. All other steps are the same.

[0094] Comparative Example 7: Compared with Example 2, the difference is that only lanthanum nitrate (Al:La molar ratio = 0:1) is used in step S4, that is, only LaAlO3 coating is generated, without LiAlO2, and the rest are the same.

[0095] Comparative Example 8: Compared with Example 2, the difference is that in step S4, instead of dissolving and evaporating aluminum nitrate and lanthanum nitrate, nano-Al2O3 powder and nano-La2O3 powder are directly weighed, physically mixed, and coated onto the surface of LiMn2O4 before high-temperature sintering. All other steps are the same.

[0096] Comparative Example 9: The difference from Example 2 is that ammonium fluoride is not added in step S2, i.e., there is no fluorine doping. Everything else is the same.

[0097] Comparative Example 10: Compared to Example 2, the difference lies in the use of 0.1 mol / L hydrochloric acid instead of tartaric acid in step S2 for acid washing, which completely removes residual lithium from the surface instead of partially retaining it. Everything else is the same.

[0098] Comparative Example 11: Compared with Example 2, the difference is that tartaric acid is not used in step S2. Instead, ammonium fluoride and LiMn2O4 powder are directly mixed in deionized water and then subjected to the same treatment (without acid washing to remove residual lithium). All other steps are the same.

[0099] Comparative Example 12: Compared with Example 2, the difference is that commercially available LiMn2O4 powder was used instead of the powder prepared in Example 1, while the other process steps were exactly the same.

[0100] Test Example 1: Experimental instructions This test case aims to verify the mechanism by which residual lithium (Li2CO3 / LiOH) on the surface is partially removed and partially retained during organic acid treatment. The residual amount of alkaline lithium compounds on the surface is indirectly reflected by measuring the pH value of the aqueous suspension of different samples.

[0101] Experimental subjects: The following 5 powder samples were selected for comparative testing: Sample A: Unmodified LiMn2O4 powder prepared in Preparation Example 1 (without any treatment) Sample B: Powder processed in step S2 of Example 1 (tartaric acid treatment, no fluorine / phosphorus doping, no subsequent activation or coating) Sample C: Powder processed in step S2 of Example 2 (treated with tartaric acid + NH4F and then directly dried, without subsequent activation or coating). Sample D: Powder after treatment in step S2 of Comparative Example 10 (treated with 0.1 mol / L hydrochloric acid instead of tartaric acid to completely remove residual lithium, with no subsequent steps). Sample E: Powder after step S2 in Comparative Example 11 (tartaric acid was not used; NH4F and LiMn2O4 were simply mixed in deionized water, with no subsequent steps). Experimental steps: Take 1.0g of each of the above powder samples and place them in five clean 50mL beakers.

[0102] Add 20 mL of deionized water (resistivity ≥ 18.2 MΩ·cm) to each beaker and stir with a magnetic stirrer at 200 rpm for 5 minutes to disperse the powder evenly.

[0103] After stopping stirring, immediately insert a pH meter (calibrated at three points with standard buffer solutions of pH=4.00, 6.86, and 9.18 before use) about 1 cm below the surface of the suspension. Record the pH value after the reading stabilizes for 30 seconds.

[0104] Repeat the above operation 3 times for each sample (each time a new sample is taken), record the measurement value each time, and calculate the mean and standard deviation.

[0105] All operations were performed in a constant temperature chamber at 25±1℃. Before each measurement, the pH meter electrode was cleaned with deionized water and dried with filter paper.

[0106] Experimental data Table 1. pH value measurement results of aqueous suspensions for each sample. ; Attached Figure Description

[0107] Figure 1 This is a comparison graph of the pH values ​​of LiMn2O4 powder aqueous suspensions under different treatment conditions according to the present invention. The horizontal axis represents five samples: A is unmodified LiMn2O4 powder, B is powder treated with tartaric acid, C is powder treated with a mixture of tartaric acid and NH4F, D is powder after complete removal of residual lithium with hydrochloric acid, and E is powder treated with NH4F only without acid washing. The vertical axis represents the pH value of the suspension, and the error bars represent the standard deviation of three measurements. The two horizontal dashed lines represent the pH of pure water (neutral) at pH=7 and the strong alkalinity threshold at pH=9, respectively.

[0108] According to the data in Table 1, the pH value of the aqueous suspension of unmodified LiMn2O4 powder (sample A) was as high as 10.95, indicating that a large amount of alkaline residual lithium compounds (LiOH and Li2CO3) were present on its surface. After treatment with tartaric acid (samples B and C), the pH value dropped significantly to 8.64 and 8.55, respectively, indicating that most of the residual lithium on the surface had been neutralized and removed by acid, but it was still maintained in the weakly alkaline range (pH>8), which means that about 10% to 50% of the residual lithium was retained. Compared with sample D (completely removed by hydrochloric acid), the pH value of sample D was 6.95, which was close to neutral, indicating that the residual lithium was almost completely removed. The pH value of sample E (treated only with NH4F aqueous solution, without the use of organic acid) was 10.41, which was only slightly lower than that of the unmodified sample, indicating that the hydrolytic acidity of ammonium fluoride alone could not effectively remove the residual lithium on the surface, nor could it create a weakly acidic environment conducive to the adsorption of subsequent coating precursors.

[0109] Test Example 2: Experimental instructions This test example verifies the in-situ formation of LiAlO2 using the selective leaching method with dilute hydrochloric acid. LiAlO2 can react with dilute hydrochloric acid to form water-soluble Li... + And Al 3+ By measuring the Li in the leachate + With Al 3+ The molar ratio can be used to determine the presence of the LiAlO2 phase. The theoretical molar ratio is 1:1. If Li + Far more than Al 3+ This indicates the presence of free Li₂CO₃ / LiOH on the sample surface; if Al 3+ Far more than Li + If the molar ratio is close to 1:1, then the presence of LiAlO2 can be confirmed.

[0110] Experimental subjects: The following three powder samples were selected: Sample F: The final product of Example 1 (modified LiMn2O4 treated with tartaric acid in S2, activated in S3, and sintered with a coating in S4, containing Al but not La, with LiAlO2 expected to be generated in the coating). Sample G: Final product of Comparative Example 4 (Skipping S2 acid washing and S3 activation, directly sintering the S4 coating on unmodified LiMn2O4, only depositing Al2O3, with no residual lithium participating in the reaction) Sample H: Final product of Comparative Example 8 (S2 and S3 are skipped; in S4, nano-Al2O3 and La2O3 powders were physically mixed and coated before sintering, without in-situ chemical reaction to generate LiAlO2) Experimental steps: Weigh 0.500g of each of the three powders and place them in three 50mL centrifuge tubes.

[0111] Add 20 mL of 0.1 mol / L dilute hydrochloric acid (prepared from analytical grade hydrochloric acid) to each centrifuge tube. After sealing, place the tubes in a constant temperature water bath shaker and shake at 150 rpm for 30 minutes at 25 ± 1 °C.

[0112] After shaking, the suspension was centrifuged at 4000 rpm for 10 minutes, and the supernatant was filtered through a 0.22 μm aqueous filter membrane into a clean sample bottle.

[0113] The concentrations of Li and Al in the filtrate were simultaneously determined using an inductively coupled plasma optical emission spectrometer (ICP-OES, PerkinElmerAvio200). Standard curves were established using mixed standard solutions of Li and Al (0.1, 0.5, 1.0, 5.0, and 10.0 mg / L), with a detection limit of 0.01 mg / L.

[0114] Calculate the leaching amount (μmol / g) of Li and Al per gram of powder based on the leaching volume and sample weight. Determine the Li / Al molar ratio using the molar ratio.

[0115] Each sample was tested independently three times, and the mean and standard deviation were calculated.

[0116] Experimental data Table 2. Molar ratio of Li to Al in the dilute hydrochloric acid leachate of each sample ; Attached Figure Description

[0117] Figure 2This is a comparison graph showing the stoichiometric ratio (Li / Al molar ratio) of acid-soluble Li and Al on the surface of LiMn2O4 under different process conditions of this invention. The horizontal axis represents three samples: F is Example 1 (modified LiMn2O4 prepared using a complete acid washing-activation-coating process), G is Comparative Example 4 (skipping the acid washing and activation steps, directly depositing an Al2O3 coating on unmodified LiMn2O4), and H is Comparative Example 8 (sintering after physically mixing nano-Al2O3 and La2O3 on unmodified LiMn2O4). The vertical axis represents the Li / Al molar ratio; error bars represent the standard deviation of three independent measurements; black dots represent the original data from the three measurements; and the horizontal dashed line indicates the position where the theoretical Li / Al molar ratio is equal to 1:1 when LiAlO2 dissolves.

[0118] According to the data in Table 2, the Li / Al molar ratio of sample F in Example 1 was 1.010, which is highly consistent with the theoretical molar ratio of LiAlO2 (1:1) within the experimental error range. This indicates that the treatment process in Example 1, including the partial removal of residual lithium from the surface with organic acid, low-temperature activation to form surface pores, and subsequent sintering of the aluminum-containing coating, did indeed promote a solid-phase reaction between the residual lithium on the surface and the deposited Al2O3, resulting in the in-situ formation of LiAlO2. It is noteworthy that the total leaching amount of Li and Al in sample F (approximately 8.2 μmol / g for Li and approximately 8.1 μmol / g for Al) was much lower than the total Al content in the simple Al2O3 coating, indicating that the generated LiAlO2 was distributed on the particle surface in the form of a nanolayer, rather than a bulk structure.

[0119] Test Example 3: Experimental instructions This test example involves immersing different samples in LiPF6 electrolyte at high temperature for accelerated aging, and measuring the concentration of Mn ions dissolved in the electrolyte to verify the presence of fluorine (F). - ) or containing phosphorus (PO4) 3- The inhibitory effect of the interface deposition layer on Mn dissolution. The lower the amount of Mn dissolution, the stronger the stabilizing effect of the interface layer on Mn ions.

[0120] Experimental subjects: The following four final product powder samples were selected: Sample I: Final product of Example 1 (S2 treated with tartaric acid, no fluorine / phosphorus doping, S3 activated, S4 coated) Sample J: Final product of Example 2 (S2 treated with tartaric acid + NH4F, S3 activated, S4 coated). Sample K: Final product of Example 3 (S2 treated with citric acid + NH4H2PO4, S3 activated, S4 coated). Sample L: Final product of Comparative Example 9 (S2 was treated with tartaric acid and contained no NH4F, S3 was activated, S4 was coated, and there was no fluorine doping compared with Example 2; the rest of the processes were the same) Experimental steps: Prepare LiPF6 electrolyte in an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm): Dissolve lithium hexafluorophosphate (LiPF6, battery grade, purity ≥ 99.9%) in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) in a volume ratio of 1:1:1 to prepare a solution with a concentration of 1.0 mol / L.

[0121] Weigh 1.000g of each of the above four powder samples and place them in four 20mL borosilicate glass sample bottles.

[0122] Add 10 mL of the prepared electrolyte to each sample vial, seal it, and then remove it. Reseal the vial opening with PTFE tape. All operations should be performed in a glove box.

[0123] Place the sealed sample vials in a constant temperature oven and store them at 45±1℃ for 14 days. During this period, take them out every 2 days and use a disposable syringe to draw about 0.5 mL of the supernatant in a glove box. Filter the supernatant through a 0.22 μm polytetrafluoroethylene filter membrane into the sample tube.

[0124] The concentration of Mn in the filtrate at each time point was determined using inductively coupled plasma optical emission spectrometry (ICP-OES, PerkinElmerAvio200). A standard curve was established using Mn standard solutions (0.05, 0.1, 0.5, 1.0, and 5.0 mg / L), with a detection limit of 0.01 mg / L.

[0125] Based on the electrolyte volume and sample weight, calculate the cumulative Mn dissolution amount (μg / g) per gram of powder at the corresponding time point. Plot a dissolution curve with dissolution time on the x-axis and cumulative Mn dissolution amount on the y-axis.

[0126] Each sample was tested independently twice, and the average value was taken as the final data at that time point.

[0127] Experimental data Table 3. Data on the cumulative Mn dissolution of each sample in LiPF6 electrolyte at 45℃ over time. ; Attached Figure Description

[0128] Figure 3This is a graph showing the cumulative Mn dissolution curves of LiMn2O4 in a 45℃ LiPF6 electrolyte under different interfacial doping conditions, as a function of storage time. The horizontal axis represents storage time (0–14 days), and the vertical axis represents the cumulative mass of Mn ions dissolved per gram of powder (μg / g). The four curves represent: Sample I (Example 1, S2 treated with tartaric acid, no fluorine or phosphorus doping), Sample J (Example 2, S2 treated with tartaric acid + NH4F, fluorine doping), Sample K (Example 3, S2 treated with citric acid + NH4H2PO4, phosphorus doping), and Sample L (Comparative Example 9, S2 treated with tartaric acid, no fluorine or phosphorus doping, only lacking fluorine doping compared to Example 2). Error bars indicate the deviation range of two independent repeated tests.

[0129] According to the data in Table 3, Mn dissolution occurred in all samples in the LiPF6 electrolyte. This is because Mn... 3+ Disproportionation reaction (2Mn) 3+ →Mn 2+ +Mn 4+ This is an inevitable result. However, the dissolution rate and accumulation of Mn under different interface doping conditions show significant differences.

[0130] After 14 days of storage, the cumulative Mn leaching amount was 17.34 μg / g for sample J (fluorine-doped), 16.64 μg / g for sample K (phosphorus-doped), 31.95 μg / g for sample I (undoped control), and even reached 34.95 μg / g for sample L (comparative example 9). Using F... - Or PO4 3- The Mn leaching amount in the sample with interface deposition decreased by approximately 45% to 52% compared to the undoped sample. Considering that the only difference between sample I and sample J is the addition of NH4F in step S2, this result directly confirms the inhibitory effect of the fluoride interface layer on Mn leaching.

[0131] The dissolution curves show that the dissolution rate of each sample was relatively fast in the first four days, after which the curves gradually flattened. This is determined by the initial dissolution of surface-active Mn sites and the subsequent slowdown in diffusion. In the initial stage of days 0–2, the dissolution amounts of samples J and K were significantly lower than those of samples I and L, indicating that the interfacial layer began to play a protective role in the early stages of contact with the electrolyte. From day 4 to day 14, the average dissolution rate of the doped samples (approximately 0.9–1.0 μg·g⁻¹) was [not specified in the original text]. -1 ·sky -1 The concentration was also significantly lower than that of the undoped sample (approximately 1.8–2.0 μg·g). -1 ·sky -1 ), indicating F - and PO4 3- The stabilizing effect on Mn ions is a continuous rather than a transient effect.

[0132] Comparing the data of samples J and K, the Mn dissolution amounts at various time points were not significantly different, differing by only 0.7 μg / g after 14 days. This indicates that under the conditions of this process, the fluoride and phosphate interfacial layers had comparable inhibitory effects on Mn dissolution. However, in absolute terms, the phosphorus-doped sample K showed slightly lower dissolution amounts than the fluorine-doped sample J at most time points, possibly due to the presence of PO4. 3- With Mn 2+ This is related to the formation of a more insoluble manganese phosphate precipitate.

[0133] Test Example 4: Experimental instructions This test case indirectly evaluates the impact of the activation step on coating adhesion by comparing the long-term cycling capacity retention rates of samples with and without the activation step. If the activation step enhances the mechanical anchoring between the coating and the substrate by creating surface nanopores, the coating is less likely to detach during long cycles, and the capacity decay rate should be slower.

[0134] Experimental subjects: The following two final product powder samples were selected: Sample M: ​​Final product of Example 2 (complete process, including S2 tartaric acid + NH4F treatment, S3 activation, and S4 coating sintering) Sample N: Final product of Example 7 (Compared with Example 2, the S3 activation step was skipped, and the rest of the process was the same) Experimental steps: Samples M and N were used as positive electrode active materials, respectively, and were mixed with conductive carbon black (SuperP) and polyvinylidene fluoride (PVDF) binder at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) was added and the mixture was ground evenly to form a slurry.

[0135] The slurry was evenly coated onto the aluminum foil current collector using a scraper, and after vacuum drying at 60°C for 12 hours, it was punched into circular electrode sheets with a diameter of 12 mm. Six parallel electrode sheets were prepared for each sample.

[0136] CR2032 coin cells were assembled in an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). A lithium metal sheet was used as the counter electrode, a Celgard 2500 polypropylene membrane as the separator, and a 1.0 mol / L LiPF6 EC / DEC / EMC (volume ratio 1:1:1) solution as the electrolyte. Approximately 80 μL of electrolyte was injected into each cell.

[0137] The assembled batteries were left to stand for 12 hours to allow the electrolyte to fully impregnate them, and then constant current charge-discharge cycle tests were performed on the LANDCT2001A battery testing system. The voltage window was 3.0–4.3V (vs. Li). + / Li), the test temperature was 25±1℃.

[0138] The cycling test procedure is as follows: First, perform one activation cycle at a rate of 0.1C (1C=148mA / g); then perform 200 constant current charge-discharge cycles at a rate of 0.5C. Record the discharge specific capacity (mAh / g) for each cycle.

[0139] Using the discharge specific capacity of the first 0.5C cycle as a benchmark, the capacity retention rate (%) for each cycle was calculated. The average value of the test results of 6 parallel cells was taken for each sample.

[0140] To further analyze the capacity decay trend, the capacity retention rate of the 50th, 100th, 150th and 200th cycles relative to the 0.5C of the 1st cycle was recorded, and the average capacity decay rate (% / cycle) per cycle of adjacent intervals (0–50 cycles, 50–100 cycles, 100–150 cycles, 150–200 cycles) was calculated.

[0141] Experimental data Table 4. Capacity retention data of samples with and without activation steps (Example 2) during 0.5C cycling. ; Table 5 Comparison of average capacity decay rates in different intervals ; Table 6 Summary of Capacity Retention Rate at Specific Cycle Numbers ; Attached Figure Description

[0142] Figure 4 This is a comparative graph showing the effect of the activation step on the capacity retention of LiMn2O4 at a 0.5C rate in this invention. The horizontal axis represents the number of cycles (0–200), and the vertical axis represents the capacity retention (%) relative to the first 0.5C cycle. The black dotted lines represent the data for sample M (Example 2, complete process including S3 activation step), and the gray square lines represent the data for sample N (Example 7, skipping S3 activation step). The error bars represent the standard deviation of the test results for six parallel cells. The dashed line in the graph is the linear fitting trend line from the data points of cycle 1 to cycle 200, used to visually compare the average decay rate of the two curves; the corresponding average decay rate value per cycle is marked next to the fitted line.

[0143] in conclusion According to the data in Table 4, Example 2 (including the activation step) and Example 7 (without the activation step) exhibited significant performance differences after 200 cycles at 0.5C. Example 2 maintained a capacity retention of 86.78% after 200 cycles, while Example 7 (without the activation step) only maintained 75.95%, a difference of 10.83 percentage points. As shown in Table 6, this difference did not suddenly appear in the later stages of cycling. After 50 cycles, the retention rate of Example 2 was 96.87%, and that of Example 7 was 94.05%, a difference of only 2.82 percentage points; after 100 cycles, the difference widened to 5.37 percentage points; and after 150 cycles, the difference further widened to 7.95 percentage points. This trend of the difference increasing with the number of cycles is a key clue for understanding the role of the activation step.

[0144] Analysis of the average capacity decay rate in each interval of Table 5 reveals that the decay rate of Example 2 remained relatively stable between 0.065 and 0.071% per cycle, without any significant accelerated decay behavior. In contrast, the decay rate of Example 7 fluctuated between 0.116 and 0.126% per cycle, approximately 1.8 times that of Example 2. More importantly, the decay rate of Example 7 did not increase significantly with cycling, but remained at a high level from the beginning. This phenomenon indicates that the absence of the activation step did not cause the coating to suddenly detach at a certain point in time, but rather resulted in insufficient initial adhesion between the coating and the substrate, exhibiting a higher decay rate from the initial stage of cycling.

[0145] Test Example 5: Experimental instructions This test case compares the rate performance and long-cycle stability of the composite coating (LiAlO2+LaAlO3) with those of single LiAlO2 and single LaAlO3 coatings to verify the synergistic effect between LiAlO2 and LaAlO3. Theoretically, LiAlO2, as a fast ion conductor, provides low impedance Li... + The transport channel is beneficial for capacity utilization at high rates; LaAlO3, as a rigid perovskite structure, suppresses Jahn-Teller distortion and lattice volume changes, which is beneficial for cycle retention. The combination of the two should simultaneously improve rate capability and cycling performance.

[0146] Experimental subjects: The following three final product powder samples were selected: Sample O: Final product of Example 2 (complete process, including LiAlO2 and LaAlO3 composite coating, Al:La molar ratio = 1:1) Sample P: Final product of Comparative Example 6 (S4 coating only uses aluminum nitrate solution, Al:La=1:0, only LiAlO2 coating is generated, the rest is the same as in Example 2) Sample Q: Final product of Comparative Example 7 (S4 coating only uses lanthanum nitrate solution, Al:La=0:1, only LaAlO3 coating is generated, the rest is the same as in Example 2) Experimental steps: Samples O, P, and Q were used as positive electrode active materials, respectively. A slurry was prepared using NMP as solvent according to the mass ratio of positive electrode material:SuperP:PVDF=8:1:1. The slurry was coated on aluminum foil, dried under vacuum at 60℃, and then punched into electrode sheets with a diameter of 12mm. Eight parallel electrode sheets were prepared for each sample.

[0147] CR2032 coin cells were assembled in a glove box, with lithium metal sheets as the counter electrode, 1 mol / L LiPF6 / EC+DEC+EMC (1:1:1) as the electrolyte, and Celgard2500 as the separator. Each cell was filled with 80 μL of electrolyte.

[0148] After the battery was left to stand for 12 hours, rate performance tests were performed on the LANDCT2001A test system: at 25°C, five charge-discharge cycles were performed at each of the following rates: 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C (voltage range 3.0–4.3V). Finally, the battery was returned to 0.1C for five cycles, and the average discharge specific capacity of the last three cycles at each rate was recorded.

[0149] Another set of batteries was selected for cycle stability testing: first, the batteries were activated once at 0.1C, and then constant current charge and discharge was performed 200 times at 0.5C. The capacity of the first 0.5C discharge and the capacity of the 200th discharge were recorded, and the capacity retention rate was calculated.

[0150] For each sample rate test, four parallel cells were used, and for the cycle test, another four parallel cells were used. The results were calculated as the average and standard deviation.

[0151] Experimental data Table 7. Discharge specific capacity (mAh / g) of the three coated samples at different discharge rates. ; Table 8. Capacity retention (%) of the three coated samples after 200 cycles at 0.5C. ; Figure 5This is an electrochemical verification diagram of the synergistic effect of LiAlO2 and LaAlO3 in this invention. Subplot (a) shows the discharge specific capacity curves at different rates, with the horizontal axis representing the rate (0.1C, 0.2C, 0.5C, 1C, 2C, 5C and returning to 0.1C) and the vertical axis representing the discharge specific capacity (mAh / g). The three curves represent: Sample O (Example 2, LiAlO2+LaAlO3 composite coating, solid black dot), Sample P (Comparative Example 6, LiAlO2 coating only, solid gray square), and Sample Q (Comparative Example 7, LaAlO3 coating only, solid light gray triangle). Subplot (b) is a bar chart of capacity retention after 200 cycles at 0.5C, with the horizontal axis representing the coating type and the vertical axis representing the capacity retention (%). Each bar corresponds to the average value of the sample, the error bars represent the standard deviation of 8 parallel cells, and the black scatter dots represent the original test values ​​of each cell.

[0152] According to the data in Tables 7 and 8, the composite coating sample O is superior to the single coating samples P and Q in both rate performance and cycle stability.

[0153] From the rate performance perspective (Table 7), the discharge specific capacity of the three samples is not significantly different at 0.1C: Sample O is 122.5 mAh / g, Sample P is 121.4 mAh / g, and Sample Q is 119.7 mAh / g, with differences within 3%, indicating that the coating type has a limited impact on capacity at low rates. However, the difference widens significantly as the rate increases. At 2C, Sample O has a capacity of 99.5 mAh / g, Sample P has 92.5 mAh / g, and Sample Q is only 86.2 mAh / g; at 5C, Sample O still has 85.4 mAh / g, while Sample P drops to 75.5 mAh / g, and Sample Q is only 67.1 mAh / g. Calculated based on the 5C / 0.1C rate retention rate, Sample O has 69.7%, Sample P has 62.2%, and Sample Q is only 56.1%. Sample Q (LaAlO3 only) has the lowest capacity at high rates because LaAlO3 itself is an electronic insulator and has poor ionic conductivity, lacking the fast ionic conductor LiAlO2 to provide low impedance Li +Transport Channels. Sample P (LiAlO2 only) exhibited better rate performance than Q but significantly worse than O, suggesting that LaAlO3 in the composite coating did not impair rate performance but rather improved it. A possible reason is that LiAlO2 and LaAlO3 formed an interconnected composite structure in the coating, and the rigid framework of LaAlO3 helped maintain the overall structural integrity of the coating, indirectly protecting the ion channels of LiAlO2 from cyclic stress damage. Furthermore, upon returning to 0.1C testing, all samples recovered most of their capacity: sample O at 121.2 mAh / g (98.9%), P at 119.1 mAh / g (98.1%), and Q at 117.2 mAh / g (97.9%). This indicates that the capacity loss during rate testing was mainly a reversible change caused by polarization, rather than material structural damage.

[0154] From the perspective of cycle stability (Table 8), sample O retained 86.8% of its capacity after 200 cycles at 0.5C, sample P retained 78.0%, and sample Q retained 82.2%. Sample P had the lowest capacity retention rate. This is because although the LiAlO2 coating alone exhibits good ion conductivity, the mechanical strength of LiAlO2 itself is insufficient. + The lattice stress generated by repeated insertion and extraction can easily lead to coating cracking or peeling, resulting in a decline in protective performance. Sample Q exhibits better capacity retention than P but worse than O, indicating that LaAlO3, as a rigid perovskite oxide, can partially suppress the volume changes caused by Jahn-Teller distortion. However, the lack of LiAlO2 to assist ion transport leads to increased interfacial polarization, indirectly affecting capacity retention. The composite coating sample O combines the advantages of both: LiAlO2 ensures rapid ion transport, while LaAlO3 provides structural support. The two do not simply represent a performance additive effect but rather a synergistic enhancement. Regarding the data dispersion of parallel samples, the standard deviation of sample O is 0.32%, less than 0.37% for P and 0.30% for Q (Q has the lowest dispersion), indicating good process repeatability of the composite coating.

[0155] Test Example 6: Experimental instructions This test case compares the charging specific capacity, discharging specific capacity, and coulombic efficiency of each embodiment of the present invention with those of the comparative example during the first charge and discharge process to verify whether the processing technology of the present invention (including organic acid treatment, activation, coating sintering, and doping) causes irreversible damage to the intrinsic capacity of LiMn2O4, and whether the removal of residual lithium on the surface reduces the first irreversible capacity loss.

[0156] Experimental subjects: The following 9 final product powder samples were selected: Example 1 (Standard process, no doping) Example 2 (Standard process + F doping) Example 3 (Standard process + P doping) Example 4 (Standard process + F / P dual doping) Comparative Example 1 (Unmodified LiMn2O4, i.e., Preparation Example 1) Comparative Example 4 (skipping S2 pickling and S3 activation, direct coating) Comparative Example 5 (treated with excess 0.5 mol / L tartaric acid, almost all residual lithium was removed) Comparative Example 9 (Compared to Example 2, S2 does not contain NH4F and has no F doping) Comparative Example 10 (residual lithium was completely removed using 0.1 mol / L hydrochloric acid, with no subsequent doping) Experimental steps: 0.2000 g of each sample powder was weighed and ground in an agate mortar for 30 minutes with an appropriate amount of NMP according to the mass ratio of positive electrode material:SuperP:PVDF=8:1:1 to form a uniform slurry. The slurry was then coated onto aluminum foil using a 100 μm scraper and vacuum dried at 60℃ for 12 hours before being cut into 12 mm diameter electrode sheets. Five parallel electrode sheets were prepared for each sample.

[0157] CR2032 coin cells were assembled in an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). A lithium metal sheet was used as the counter electrode, Celgard 2500 as the separator, and 1.0 mol / L LiPF6 / EC+DEC+EMC (volume ratio 1:1:1) was used as the electrolyte, with 80 μL of electrolyte injected into each cell. The cells were then allowed to stand for 12 hours after assembly.

[0158] The first charge-discharge test was conducted using the LANDCT2001A battery test system. The voltage range was set to 3.0–4.3V (vs. Li). + / Li), with a rate of 0.1C (1C=148mA / g). First, charge at a constant current to 4.3V, then charge at a constant voltage until the current drops to 0.01C, and then discharge at a constant current of 0.1C to 3.0V. Record the specific capacity of the first charge (mAh / g) and the specific capacity of the first discharge (mAh / g), and calculate the first coulombic efficiency (discharge capacity / charge capacity × 100%).

[0159] For each sample, test results from 5 parallel cells were taken, and the mean and standard deviation were calculated.

[0160] Experimental data Table 9. Initial charge-discharge performance data of each sample at 0.1C ; Attached Figure Description

[0161] Figure 6This is a comparison chart of the initial charge and discharge performance of different embodiments and comparative examples of the present invention. Sub-figure (a) is a grouped bar chart of specific capacity for initial charge and discharge. In each group, the light gray bar on the left represents the charging capacity, and the dark gray bar on the right represents the discharging capacity. The vertical axis represents the specific capacity (mAh / g), and the horizontal axis represents the sample name. Sub-figure (b) is a bar chart of initial coulombic efficiency. The gray bars represent the average value of each sample, the error bars represent the standard deviation, and the horizontal dashed line marks the 95% reference line.

[0162] According to the data in Table 9, Comparative Example 1 (unmodified LiMn2O4), without any treatment, had the highest initial charge capacity (131.2 mAh / g), but its initial discharge capacity was only 118.3 mAh / g, with an initial coulombic efficiency as low as 90.2%. This is mainly because there are a large number of alkaline residual lithium compounds on its surface. During the first charge, these impurities will undergo irreversible side reactions with the electrolyte, consuming some lithium ions and resulting in an irreversible capacity loss of up to about 9.8%. The coulombic efficiency of Comparative Example 4 (skipping acid washing and activation) was slightly improved to 92.1%, but it was still low, indicating that although the direct coating can isolate surface impurities to a certain extent, it cannot eliminate side reactions.

[0163] Test Example 7: Experimental instructions This test case compares the surface residual lithium content and initial electrochemical performance of samples treated with S2 using different organic acids to verify the influence of organic acid type on surface cleaning effect and subsequent performance. Different organic acids (tartaric acid, citric acid, oxalic acid, acetic acid) differ in acid strength, chelating ability, and thermal decomposition behavior, which may affect the removal efficiency of residual lithium and the quality of coating formation.

[0164] Experimental subjects: The following four final product powder samples were selected (all samples underwent the same S3 activation and S4 coating sintering steps, only the type of organic acid used in the S2 step was different): Sample R: Example 1 (S2 was treated with 0.2 mol / L tartaric acid) Sample S: Example 3 (S2 was treated with 0.2 mol / L citric acid) Sample T: Comparative Example 11 (S2 was treated with 0.2 mol / L oxalic acid) Sample U: Comparative Example 12 (S2 was treated with 0.2 mol / L acetic acid) Experimental steps: Take 0.3000 g of each of the four sample powders and place them in 15 mL centrifuge tubes. Add 8.0 mL of deionized water to each centrifuge tube, sonicate for 5 minutes, and then let stand in a 25°C constant temperature water bath for 30 minutes, shaking once every 10 minutes during this period. This step is used to extract unreacted lithium compounds (such as Li2CO3, LiOH) and water-soluble lithium salts remaining on the sample surface.

[0165] After settling, the suspension was centrifuged at 4000 rpm for 10 minutes. The supernatant was filtered through a 0.22 μm aqueous filter membrane, and the concentration of Li in the filtrate was determined using inductively coupled plasma optical emission spectrometry (ICP-OES). The amount of Li eluted per gram of sample (μmol / g) was calculated based on the extraction volume and sample weight. A higher value indicates more residual lithium on the surface. Each sample was tested independently three times.

[0166] On the other hand, coin cells of the above four samples were assembled according to steps 1–3 in Test Example 6, and a first charge-discharge test at 0.1C (voltage 3.0–4.3V) was performed. The first charge capacity, first discharge capacity, and first coulombic efficiency were recorded. Five parallel cells were tested for each sample.

[0167] Experimental data Table 10. Surface residual lithium content and initial charge-discharge performance of samples treated with different organic acids. ; Attached Figure Description

[0168] Figure 7 This is a comparative chart showing the effects of different types of organic acids on the removal of residual lithium on the surface of LiMn2O4 and its initial electrochemical performance in this invention. Sub-figure (a) is a bar chart of Li dissolution by water washing. The vertical axis represents the amount of Li that can be dissolved in water per gram of powder (μmol / g), which indirectly reflects the content of residual lithium compounds on the sample surface. The horizontal axis represents the four types of organic acid treatment: tartaric acid (Example 1), citric acid (Example 3), oxalic acid (Comparative Example 11), and acetic acid (Comparative Example 12). Sub-figure (b) is a bar chart of the initial coulombic efficiency of the corresponding sample. The vertical axis represents the ratio of initial discharge capacity to initial charge capacity (%), and the black scatter dots represent the original test results of each parallel battery.

[0169] According to the data in Table 10, different organic acids showed significant differences in their ability to remove residual lithium from the LiMn2O4 surface, and this difference directly affected the initial electrochemical performance of the material. The amount of lithium dissolved by the water washing method can be regarded as the total amount of lithium compounds remaining on the sample surface after organic acid treatment and subsequent activation and coating sintering.

[0170] The oxalic acid-treated sample (T) showed the lowest lithium dissolution rate, at only 0.11 μmol / g, indicating that oxalic acid is a strong acid (pKa1=1.23), capable of reacting with surface Li2CO3 / LiOH to form soluble lithium oxalate, which is further decomposed during the sintering process, resulting in almost complete removal of residual lithium. The citric acid-treated sample (S) showed a lithium dissolution rate of 0.38 μmol / g, while the tartaric acid-treated sample (R) showed 0.48 μmol / g, which are relatively close, indicating that these two weak organic acids have moderate removal capabilities for residual lithium, retaining some for subsequent LiAlO2 formation. The acetic acid-treated sample (U) showed a high lithium dissolution rate of 1.22 μmol / g. This is because although acetic acid is a stronger acid than tartaric acid (pKa=4.76), its solubility for Li2CO3 is poor (resulting in lower solubility of lithium acetate). Furthermore, acetic acid is easily volatilized during subsequent sintering and cannot fix lithium ions through chelation like oxalic acid and citric acid. Therefore, a large amount of residual lithium remains on the surface in the form of lithium carbonate, etc.

[0171] The acetic acid-treated sample U exhibited the lowest coulombic efficiency (92.0%), consistent with its highest residual lithium content, as excessive surface lithium compounds undergo irreversible decomposition during the first charge. Although the oxalic acid-treated sample T had very little residual lithium, its coulombic efficiency (95.6%) was on par with the citric acid-treated sample S (95.6%), not higher, indicating that lower residual lithium is not always better. Excessive removal of residual lithium (such as oxalic acid treatment) may expose more active lattice sites on the surface, which may undergo additional side reactions with the electrolyte during the first charge, thus limiting further improvement in coulombic efficiency. The citric acid and tartaric acid-treated samples S and R both showed high coulombic efficiencies (95.6% and 94.7%, respectively) while maintaining high initial discharge capacities (123.1 and 122.4 mAh / g), demonstrating a balance between residual lithium removal and surface protection.

[0172] In terms of absolute initial discharge capacity, the citric acid sample S (123.1 mAh / g) was slightly higher than the tartaric acid sample R (122.4 mAh / g), while the oxalic acid sample T (121.5 mAh / g) and the acetic acid sample U (120.1 mAh / g) decreased successively. The tricarboxylic acid structure of citric acid may have produced an additional etching effect on the surface during activation, helping to increase the binding sites for subsequent coatings, thus slightly improving capacity release. Although oxalic acid treatment resulted in the lowest residual lithium, surface defects may have appeared due to excessive cleaning, reducing structural integrity and causing a slight decrease in capacity. Acetic acid treatment, on the other hand, had the lowest discharge capacity due to excessive residual lithium and irreversible reactions consuming some active lithium.

[0173] In summary, both citric acid and tartaric acid exhibit good overall performance in the process system of this invention, with citric acid showing slightly better coulombic efficiency and discharge capacity than tartaric acid. While oxalic acid can completely remove residual lithium, it fails to further improve performance and instead exhibits capacity loss due to potential damage to the surface structure. Acetic acid has the worst treatment effect and is unsuitable for this process. Therefore, selecting an organic acid with moderate acidity and a certain chelating ability is key to achieving optimal performance, rather than simply pursuing complete removal of residual lithium.

[0174] Test Example 8: Experimental instructions This test example prepared a series of composite coating samples with different Al:La molar ratios by changing the molar ratio of Al(NO3)3 and La(NO3)3 in the coating precursor solution, and tested their rate performance and cycle stability to determine the optimal Al:La ratio. The Al:La ratio directly affects the phase distribution and relative content of LiAlO2 and LaAlO3 in the coating, and thus affects the balance between ionic conductivity and structural stability.

[0175] Experimental subjects: The following 5 final product powder samples were selected (all samples were prepared according to the complete process of Example 2, with only Al adjusted in step S4). 3+ and La 3+ (molar ratio) Sample V:Al:La molar ratio = 1:0 (LiAlO2 coating only, Comparative Example 6) Sample W:Al:La molar ratio = 3:1 Sample X: Al:La molar ratio = 1:1 (Example 2) Sample Y:Al:La molar ratio = 1:3 Sample Z: Al:La molar ratio = 0:1 (LaAlO3 coating only, Comparative Example 7) Experimental steps: Weigh Al(NO3)3·9H2O and La(NO3)3·6H2O according to the above proportions, and dissolve them in deionized water to prepare 50 mL of a 0.2 mol / L (based on total metal ions) mixed nitrate solution. Add 10 g of S3-activated LiMn2O4 powder to the solution, stir and impregnate in a 60°C water bath for 1 hour, and then evaporate the moisture in a 120°C oven.

[0176] The dried powder was placed in a tube furnace and sintered in air at a rate of 5°C / min to 650°C for 3 hours, so that Al 3+ and La 3+ In-situ generation of LiAlO2 and LaAlO3 composite coating.

[0177] Assemble coin cells according to the method described in Test Example 5, and conduct rate tests (0.1C, 0.2C, 0.5C, 1C, 2C, 5C) and a 200-cycle test at 0.5C. Test results for five parallel cells of each sample are collected. To eliminate batch variations, all samples were prepared and tested in the same experiment.

[0178] Experimental data Table 11 Rate performance and cycle retention data for samples with different Al:La molar ratios ; Attached Figure Description

[0179] Figure 8 This is a comparison chart of the effects of different Al:La molar ratios on the electrochemical performance of the LiMn2O4 composite coating in this invention. Sub-figure (a) is a line graph of discharge specific capacity at 0.1C, 1C, and 5C rates, with the horizontal axis representing the Al:La molar ratio (1:0, 3:1, 1:1, 1:3, 0:1) and the vertical axis representing the discharge specific capacity (mAh / g). Black dots represent 0.1C, gray squares represent 1C, and light gray triangles represent 5C. Sub-figure (b) is a bar graph of the capacity retention rate of the corresponding sample after 200 cycles at 0.5C rate, with the vertical axis representing the capacity retention rate (%) and the black dots representing the original test values ​​of each parallel battery.

[0180] According to the data in Table 11, the Al:La molar ratio significantly affects the electrochemical performance of the composite coating. The best overall performance was achieved at a 1:1 ratio (sample X): 0.1C capacity 122.9 mAh / g, 1C capacity 108.3 mAh / g, 5C capacity 85.4 mAh / g, and a cycle retention of 86.9% after 200 cycles. When the Al ratio increased (3:1, sample W), the 5C capacity decreased to 81.1 mAh / g, and the cycle retention dropped to 82.6%. When the La ratio increased (1:3, sample Y), the 5C capacity decreased more significantly to 77.2 mAh / g, with a cycle retention of 84.4%, slightly lower than 1:1 but better than 3:1. The performance at extreme ratios (1:0 and 0:1) deteriorated significantly, especially with 5C capacities of only 75.4 and 67.1 mAh / g, and cycle retentions of 78.3% and 82.4%, respectively.

[0181] This trend reveals the individual contributions and mutual constraints of the two components in the composite coating. LiAlO2, as a fast ion conductor, dominates rate performance; therefore, samples with a higher LiAlO2 content (W, X, V) exhibit higher capacities at both 1C and 5C than samples with a higher LaAlO3 content (Y, Z). However, sample V, containing only LiAlO2, has the lowest cycle retention (78.3%), indicating insufficient mechanical support and a tendency for coating degradation during long cycles. LaAlO3, as a rigid perovskite phase, significantly contributes to structural stability: with increasing La content (from 1:0 to 1:1 to 1:3), cycle retention rates are 78.3%, 82.6%, 86.9%, 84.4%, and 82.4%, respectively, showing a trend of first increasing and then decreasing, with the peak occurring near 1:1. The reduced retention rate at a 1:3 ratio may be due to excessive LaAlO3 leading to excessively low ion conductivity in the coating (5C capacity of only 77.2 mAh / g), resulting in intensified polarization and exacerbated interfacial side reactions, indirectly reducing cycle stability. The decrease in retention rate between the 3:1 and 1:1 ratios also supports this hypothesis: too much LiAlO2 and insufficient LaAlO3 result in a lack of sufficient structural support, leading to a rebound in the attenuation rate.

[0182] In terms of absolute values ​​of rate performance, sample X with a 1:1 ratio still exhibits 85.4 mAh / g at 5C, significantly higher than the 81.1 mAh / g of the 3:1 ratio and the 77.2 mAh / g of the 1:3 ratio. This indicates that the presence of an appropriate amount of LaAlO3 not only does not impair rate performance but may also enhance capacity at high rates by refining LiAlO2 grains or improving coating uniformity. The capacity difference between the 3:1 and 1:3 ratios at 5C further verifies the dominant role of LiAlO2, but the superior performance of the 1:1 ratio suggests a positive synergistic effect between the two phases: LiAlO2 provides ion channels, while LaAlO3 provides structural support, forming an interpenetrating network that gives the coating both high ionic conductivity and good mechanical stability.

[0183] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a composite surface-modified lithium manganese oxide cathode material, characterized in that, It includes LiMn2O4 particles as the matrix and a composite coating covering the surface of the LiMn2O4 particles; The composite coating is composed of a mixture of in-situ generated LiAlO2 and LaAlO3; A fluorine- and / or phosphorus-containing interfacial transition layer is formed between the LiMn2O4 particles and the composite coating. The positive electrode material has an initial charge-discharge coulombic efficiency of no less than 95% at a rate of 0.1C and a voltage range of 3.0–4.3V.

2. The preparation of a composite surface-modified lithium manganese oxide cathode material according to claim 1, characterized in that, The molar ratio of Al to La in the composite coating is (0.5–2):(0.5–2), and the total mass of the coating accounts for 0.5%–8% of the total mass of the cathode material.

3. The preparation of a composite surface-modified lithium manganese oxide cathode material according to claim 1, characterized in that, The fluorine- and / or phosphorus-containing interfacial transition layer is derived from at least one of the following precursors: ammonium fluoride, ammonium dihydrogen phosphate, lithium fluoride, or hydrofluoric acid. The amount of the precursor introduced into the cathode material (in terms of F or P elements) is 0.5%–4% of the mass of the LiMn2O4 matrix.

4. The preparation and application of a composite surface-modified lithium manganese oxide cathode material according to claim 1, wherein the preparation of the composite surface-modified lithium manganese oxide cathode material according to any one of claims 1-3 is characterized in that, Includes the following steps: S2. Add LiMn2O4 powder to an aqueous solution containing organic acid and fluorine and / or phosphorus compounds, stir and react at room temperature, and after the reaction is completed, separate, wash and dry to obtain an acid-treated powder with fluoride and / or phosphate deposited on the surface. S3. Place the powder obtained in S2 under an inert atmosphere and keep it at 200–350℃ for 1–3 hours for activation treatment. After cooling, the activated powder is obtained. S4. Add the activated powder to the Al-containing... 3+ and La 3+ The precursor solution was impregnated, the solvent was evaporated, and then sintered at 400–900℃ for 2–10 hours in air atmosphere to allow Al to form a precipitate. 3+ and La 3+ The cathode material is obtained by in-situ conversion into a composite coating of LiAlO2 and LaAlO3.

5. The preparation and application of a composite surface-modified lithium manganese oxide cathode material according to claim 4, characterized in that, In step S2, the organic acid is at least one selected from tartaric acid, citric acid, malic acid, oxalic acid, and acetic acid, and its amount is 0.5%–18% of the mass of LiMn2O4 powder. The fluorine-containing compound is selected from at least one of ammonium fluoride, lithium fluoride, and hydrofluoric acid; the phosphorus-containing compound is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate. The amount of the fluorine-containing compound and / or phosphorus-containing compound (based on F or P element) is 0.5%–4% of the mass of LiMn2O4 powder.

6. The preparation and application of a composite surface-modified lithium manganese oxide cathode material according to claim 4, characterized in that, In step S2, the concentration of the organic acid solution is 0.5–10 g / L, the solid-liquid ratio is 1 g:20 mL, and the stirring time is 2–4 hours.

7. The preparation and application of a composite surface-modified lithium manganese oxide cathode material according to claim 4, characterized in that, In step S3, the inert atmosphere is nitrogen, the heating rate is 3℃ / min, the activation temperature is preferably 250–300℃, and the holding time is preferably 2 hours.

8. The preparation and application of a composite surface-modified lithium manganese oxide cathode material according to claim 4, characterized in that, In step S4, the precursor solution is aluminum nitrate and lanthanum nitrate dissolved in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 1:1), with a total metal ion concentration of 0.01–0.5 mol / L. Al 3+ with La 3+ The molar ratio is (0.5–2):(0.5–2), and the total mass of the precursor (based on Al and La nitrates) is 0.1%–10% of the mass of the activated powder.

9. The preparation and application of a composite surface-modified lithium manganese oxide cathode material according to claim 4, characterized in that, In step S4, the impregnation is carried out at 60°C with ultrasonic dispersion for 2 hours, and the solvent is evaporated at 120°C with stirring.

10. The preparation and application of a composite surface-modified lithium manganese oxide cathode material according to claim 4, characterized in that, Before step S2, step S1 is also included: pre-ball milling or acid washing of LiMn2O4 powder to adjust its surface state.